Matharpacady-05.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Most of the bungalows at Matharpacady are double-storey with balconies on the first floor, supported by rows of wooden brackets. Additionally, columns on the ground floor may also support the balcony above. Most of the bungalows have wooden flooring and gable roofs covered in tiles. Such details are typical of Indo-Portuguese architecture found in other East Indian gaothans in Mumbai, like Khotachiwadi.